Real-world management of adjuvant systemic melanoma therapy: Multi-center survey of 51 DeCOG skin cancer centers - Reitmajer, Markus; Livingstone, Elisabeth; Heinzerling, Lucie; Thoms, Kai Martin; Meiss, Frank; Heppt, Markus; Gesierich, Anja; Drexler, Konstantin; Meier, Friedegund; Schlaak, Max; Forschner, Andrea; Zimmer, Lisa (Journal der Deutschen Dermatologischen Gesellschaft, 2025)
Background: Adjuvant immune checkpoint inhibitors (ICI) and targeted therapy (TT) have revolutionized treatment management for patients with melanoma. However, the current German S3 guideline does not differentiate between patients with and without adjuvant therapy in its recommendations for imaging intervals and follow-up monitoring, leading to variability in clinical practice. This study provides an overview of surveillance practices among skin cancer centers in the German Dermatologic Cooperative Oncology Group (DeCOG). Methods: A survey was sent to 80 skin cancer centers in Germany, Austria and Switzerland on November 22, 2023. Responses received by March 10, 2024 were analyzed descriptively. Results: Fifty-one responses (64%) were received. Forty centers (78%) reported deviations from the guideline. In stage IIB, 34 centers (67%) conduct imaging including CT scans prior to and after adjuvant therapy. Post-adjuvant therapy, 36 centers (71%) conduct imaging according to the guideline. Over 90% of the centers offer adjuvant ICI therapy if progression occurs on adjuvant TT and vice versa. In stage IV, after relapse while on adjuvant ICI, 32 centers (63%) would offer adjuvant TT. Conclusions: Surveillance practices differed among participating centers and often do not align with the current guideline. A consensus based consistent approach would benefit both patients and physicians.
CRIS-Team Scopus Importer:2025-12-05
Keywords: Adjuvant therapy; follow-up care; immune checkpoint inhibitor (ICI); PET/CT; recurrence; targeted therapy (TT)